2019
DOI: 10.1080/1350293x.2020.1707366
|View full text |Cite
|
Sign up to set email alerts
|

High time to put the invisible children on the agenda: supporting refugee families and children through quality ECEC

Abstract: Among asylum seekers in the EU, many are families with young children (0-4 years). In policy and practice, however, these children remain invisible. During the asylum proceedings, which can take quite some time, there is hardly any pedagogical offer available in reception centres nor are there clear policies to guarantee accessible, useful and meaningful ECEC. While there is ample evidence of the possible benefits of high quality ECEC, especially for vulnerable groups, these children often do not attend any EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
5
0
1
Order By: Relevance
“…Our findings show that the most frequent peer interactions during IGs are related to help and guidance. This outcome reveals the potential of this form of classroom organization to foster solidarity interactions among young children, even among those who might face greater challenges in education (Vandekerckhove and Aarssen 2019). In line with previous research, this study reveals that the IG format is an effective classroom organization for fostering core values, such as solidarity and empathy, through effectively promoting help and guidance interactions among peers (Díez-Palomar and Olivé 2015; García-Carrión and Díez-Palomar 2015).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings show that the most frequent peer interactions during IGs are related to help and guidance. This outcome reveals the potential of this form of classroom organization to foster solidarity interactions among young children, even among those who might face greater challenges in education (Vandekerckhove and Aarssen 2019). In line with previous research, this study reveals that the IG format is an effective classroom organization for fostering core values, such as solidarity and empathy, through effectively promoting help and guidance interactions among peers (Díez-Palomar and Olivé 2015; García-Carrión and Díez-Palomar 2015).…”
Section: Discussionsupporting
confidence: 85%
“…The results of this study revealed that the IGs format benefits children and promotes their cognitive, social, and emotional development. This is especially important in regard to Roma and children with immigrant backgrounds because of the persistent social and educational inequalities they face starting in their earliest years (Vandekerckhove and Aarssen 2019). However, there has not been in-depth research on peer interactions in interactive groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2018;Norheim & Moser 2020;Petriwskyj 2014). För föräldrarnas egen del innebär mötet med förskolans pedagoger ofta första steget i deras egen integrationsprocess ( Vandekerckhove & Aarssen 2020;Tobin 2020). Huruvida deras röster blir hörda och respekterade på förskolan kan påverka deras känsla av tillhörighet till det nya samhället (De Gioia 2015; Lunneblad 2017; Vandekerckhove & Aarssen 2020;Sønsthagen 2020;Tobin m. fl.…”
Section: Sammanfattningunclassified
“…Previous research reports on a lack of dialogue and mutual understanding between migrant parents and preschool practitioners (De Gioia 2013;Tobin 2020;Van Laere, Van Houtte, and Vandenbroeck 2018), and shows that preschool practitioners often pay inadequate attention to cultural differences (Sønsthagen 2020;Tobin 2020). Nevertheless, as early childhood education in many Western societies represents the context in which migrant families with children meet the majority society for the first time, preschools remain an important integration arena (Lunneblad 2017;Tobin 2020;Vandekerckhove and Aarssen 2019).…”
Section: Introductionmentioning
confidence: 99%